Interferon gamma inducible protein 16 (IFI16) expression is reduced in mantle cell lymphoma. Issue 11 (November 2019) - Piccaluga, Pier Paolo; Navari, Mohsen; Visani, Axel; Rigotti, Flavia; Agostinelli, Claudio; Righi, Simona; Diani, Erica; Ligozzi, Marco; Carelli, Maria; Ponti, Cristina; Bon, Isabella; Zipeto, Donato; et al.
Abstract: IFI16, member of the IFN-inducible PYHIN-200 gene family, modulates proliferation, survival and differentiation of different cell lineages. In particular, IFI16 expression, which is regulated during the differentiation of B cells, was recently studied in B-CLL as well. Here, we compared IFI16 expression in several lymphomas including Burkitt lymphoma, diffuse large B-cell lymphoma, follicular lymphoma, marginal zone lymphoma and mantle cell lymphoma with respect to normal cell counterparts. We observed that IFI16 expression was significantly deregulated only in mantle cell lymphoma (p < 0.05). Notably, IFI16 was associated with the expression of genes involved in interferon response, cell cycle, cell death and proliferation and, interestingly, lipid and glucose metabolism, suggesting that IFI16 deregulation might be associated with relevant changes in cell biology. In our group of mantle cell lymphoma samples a correlation between patient survival and IFI16 expression was not detected even though mantle cell lymphoma prognosis is known to be associated with cell proliferation. Altogether, these results suggest a complex relationship between IFI16 expression and MCL which needs to be analyzed in further studies. Abstract : Molecular biology; Cell biology; Biochemistry; Oncology; Pathology; Cancer research; Mantle cell lymphoma; Immunohistochemistry; IFI16; Proliferation; Gene expression